A computational model for static and dynamic balancing of masses on rotating shafts - Oladejo, Kolawole A.; Koya, Olufemi A.; Adekoya, Lawson O. (Computer Assisted Methods in Engineering and Science, 2008)
Balancing is the process of improving the mass distribution of a body so that it rotates in its bearings without unbalanced centrifugal forces. It is thus critical to the performance of any high speed equipment. The problem is mathematically modeled and a genetic algorithm is presented for obtaining optimal solutions for balancing problems on rotating shafts. This is eventually converted into computer package titled BALANCER, developed using the VisualBASIC platform. Examples are presented to illustrate implementation of the methodology. The model was tested by using typical problems, correctly solved in the literature using conventional methods. The results of the three examples gave same match with those obtained from analytical approach. The accuracy of analysis using the model and the students' feedback suggest that integration of the software tool will be beneficial for improving students' performance in any dynamics course.